HUBUNGAN DUKUNGAN KELUARGA DAN KUALITAS HIDUP LANSIA PENDERITA DM TIPE II DI PUSKESMAS BAKTIRAJA, HUMBANG HASUNDUTAN - Sijabat, Flora; Siregar, Rinco; Barus, Darwita J (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2023)
The impact of diabetes mellitus includes physical, psychological and social changes in sufferers. One of the common psychological changes experienced is anxiety. Support from family for people with type 2 DM in the form of emotional attention, practical assistance, and assesments provided by family members can help improving physicaly and mental well-being of sufferers and is an important form of social support. This study aims to evaluate the relationship between family support and the quality of life of elderly peopple with type 2 diabetes mellitus at the Baktiraja Health Center, Humbang Hasundutan District. This study used a quabtitative approach with a correlative descriptive method and a cross-sectional design. The research sample consisted of 65 respondents. The result showed that there was a significant relationship between family support and the quality of life of elderly people with type 2 diabetes mellitus at the Baktiraja Health center, Humbang Hasundutan District (p = 0,000). The involvement of family support for human type 2 DM has an importance role in improve heir quality of life. Therefore, health workers can provide appropriate nursing interveitions. One way that’s can be do by nurses to increase family’s support is to provide knowledge through health education and counseling to sufferers and families.